2021
DOI: 10.1186/s40795-021-00484-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and immunization status of under-five children of India and Bangladesh

Abstract: Background The nutritional and immunization status of children can play an important role in determining their future health status of a particular country. The aim of the present study is to investigate the nutritional and immunization status of under-five children in India and Bangladesh, and to find the difference in the status between these two countries. Methods We have used the National Family Health Survey data, 2015–2016 of India and Bangla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 46 publications
0
22
0
3
Order By: Relevance
“…The results of the Ethiopian privilege research showed that children from affluent families were at the lowest risk of being vaccinated compared with children from impoverished households. Studies in developing nations such as Ethiopia [17], Nigeria [29], and Bangladesh [30] back with this conclusion. The result could be because having a low salary means having less probability of getting health facilities and health workers.…”
Section: Discussionmentioning
confidence: 89%
“…The results of the Ethiopian privilege research showed that children from affluent families were at the lowest risk of being vaccinated compared with children from impoverished households. Studies in developing nations such as Ethiopia [17], Nigeria [29], and Bangladesh [30] back with this conclusion. The result could be because having a low salary means having less probability of getting health facilities and health workers.…”
Section: Discussionmentioning
confidence: 89%
“…The results of the Ethiopian privilege research showed that children from affluent families were at the lowest risk of being vaccinated compared with children from impoverished households. Studies in developing nations such as Ethiopia [ 19 ], Nigeria [ 32 ], and Bangladesh [ 33 ] back this conclusion. The result could be because having a low salary means having less probability of getting health facilities and health workers.…”
Section: Discussionmentioning
confidence: 89%
“…These results are consistent with the previous ones from East Badawacho district ( 65 ) , Butajira ( 66 ) and Dabat ( 67 ) of Ethiopia. Furthermore, children of employed mothers from poor households were more likely to be stunted, and underweight ( 68 ) . This is supported by studies from Hossana town, Ethiopia ( 69 ) , Tanzania ( 70 ) , and Northern Ghana ( 71 ) , and Nepal ( 72 , 73 ) .…”
Section: Discussionmentioning
confidence: 99%